IDENTIFIKASI MODALITAS BELAJAR VAK KOMBINASI SISWA DALAM PELAJARAN MATEMATIKA SMP NEGERI 1 ARJASA JEMBER - Dwi Novian Sulisawati; Lutfiyah; Luzainiatus Sukma (Universitas Insan Budi Utomo, 2019)
The modality of learning or what we often refer to as learning styles is one of the main factors determining the speed of students in understanding and receiving information given to them. This article aims to identify various combinations of visual, audio, and kinesthetic learning styles that exist in 8 grade of SMPN 1 ArjasaJember. This research is a descriptive study that is used as preliminary data for a research project about analyzing students problem solving based on learning styles. The data in this study were obtained through questionnaire collection that was distributed to 58 students of class 8th A grade and 8th B grade which were determined using area sampling technique. As for the questionnaire used by researchers in the process of collecting data, previously it has been declared qualitatively valid by 2 psychologists. The results showed that overall the most learning styles possessed by eighth grade students at SMP Negeri 1 Arjasa were visual learning styles with details of the percentage distribution of learning styles as follows: visual as much as 44.83%, audio as much as 31.04%, kinesthetic as much as 5.17%, visual-audio as much as 15.52%, audio-kinesthetic as much as 1.72%, and 1.72% for visual-audio-kinesthetic learning styles.